Surface plasmon resonance excited electron induction greatly extends H2 evolution and pollutant degradation activity of g‐C3N4 under visible light irradiation. Issue 6 (12th December 2019) - Zada, Amir; Ali, Nauman; Ateeq, Muhammad; Huerta‐Flores, Ali M.; Hussain, Zahid; Shaheen, Shabana; Ullah, Mohib; Ali, Sharafat; Khan, Imran; Ali, Wajid; Shah, Muhammad Ishaq Ali; Khan, Waliullah
Abstract: Energy crises and environmental pollution have sparked tremendous research work to handle their impacts. Herein, we fabricated Au/g‐C3 N4 nanocomposites to produce H2 and degrade 2, 4‐dichlorophenol (2, 4‐DCP) under visible light and at different wavelengths. Interestingly, the optimized photocatalyst generated 114 μmol H2 and degraded 25% 2, 4‐DCP in 1 hr as compared with 10 μmol H2 generation and 8% 2, 4‐DCP degradation by pure g‐C3 N4 . This improvement is credited to the extended light absorption and improved charge induction from gold to g‐C3 N4 even at 590 nm as confirmed from photoluminescence, surface photovoltage, and photoelectrochemical study of the samples. Moreover, the surface catalytic property of g‐C3 N4 was much improved after loading a proper amount of gold nanoparticles. We hope that this technique to photosensitize semiconductors with noble metal nanoparticles may provide a feasible way to construct surface plasmon resonance‐assisted photocatalysts to cope with energy crises and environmental pollution simultaneously. Abstract : Au‐loaded g‐C3 N4 nanosheets were prepared which showed enhanced photocatalytic activities for the degradation of pollutant and H2 evolution under visible light. These enhanced activities are attributed to the extended visible light absorption, improved charge separation, and surface catalysis.